The Straits Chinese Between Empires Nationalism and Cosmopolitanism in Colonial Malaya, c.1890-1920 - Jones, Christian (eCahiers de l'Institut, 2022)
This ePaper investigates the Straits Chinese community and their positioning relative to the British Empire and the Chinese Empire around 1900. It studies their responses to and interactions with the transition from a world of empires to a world of nation-states. The Straits Chinese are framed as a cosmopolitan community in a cosmopolitan city who played an important role in the reconfiguration of imperial citizenship and the deterritorialisation of China. Through their own and others' adoption of racial discourses, they found themselves in a double bind, not quite Chinese and not quite British. This shaped their encounter with early Chinese nationalism. Consequently, this paper disrupts the teleology of decolonisation and demonstrates how the transformations taking place in the international system in the early twentieth century relegated certain communities to the margins by virtue of their 'in-between' position. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.